Theoretical Studies of the Glycoluril Molecular Clips Using Quantum Calculations - Gharakhani, F.; Vessally, E.; Mohammadi, A.; Alimadadi, Z. (Asian Journal of Chemistry, 2013)
Theoretical calculations were performed to determine the structure of a simple glycoluril (1) and its derivative (2). Full geometry optimizations were carried out by MP2 method using 6-311++G** basis set of the GAUSSIAN 98 program. The geometrical parameters including bond lengths (R) and bond angles (A) were estimated at the same level.